ANALISIS KESESUAIAN TUJUAN PEMBELAJARAN DENGAN SOAL EVALUASI PADA RENCANA PELAKSANAAN PEMBELAJARAN BUATAN GURU BIOLOGI MA SULTAN HASANUDDIN KABUPATEN GOWA - Amelia, Nila; Lodang, Hamka; Saparuddin (Universitas Cokroaminoto Palopo, 2023)
This study aims to find out how appropriate the learning objectives are with the evaluation questions on the lesson plans made by biology teachers for Classes X, XI and XII MA Sultan Hasanuddin and to determine the level of distribution of cognitive levels of the revised bloom taxonomy on learning objectives for Classes X, XI and XII MA Sultan Hasanuddin. The type of research used in this study is the type of research in descriptive form. The population in this study were lesson plans and evaluation questions made by biology teachers from MA Sultan Hasanuddin, Gowa district. The results showed that for compatibility between learning objectives and evaluation questions in class X the category according to the percentage value of 64% was not in accordance with the percentage of 22%, did not correspond to the percentage of 7% and the category of finding learning objectives that did not contain 7% evaluation questions. For class XI the appropriate category is 43%, 31% less suitable, not appropriate and 0% and 26% are categories of objective findings that do not contain evaluation questions. For class XII the appropriate category is 44.5%, 44.5% inappropriate, 0% inappropriate and 11% findings of learning objectives that do not contain evaluation questions. The total distribution of learning objectives based on the cognitive level of the revised bloom taxonomy shows that category C2 with the highest percentage value is in class X 46% 50% in class XI and 25% in class XII. As for category C3 with a percentage value of 0% in all classes.